Gender Specificity and Local Socioeconomic Influence on Association of GHR fl/d3 Polymorphism With Growth and Metabolism in Children and Adolescents - Chen, Xiaotian; Liu, Chunlan; Yang, Song; Yang, Yaming; Chen, Yanchun; Zhao, Xianghai; Zhu, Weiguang; Zhao, Qihui; Ni, Chuan; Huang, Xiangyuan; Yan, Weili; Shen, Chong; et al. (Frontiers in Pediatrics, 2022)
Objective: Growth hormone receptor (GHR) mediates the majority of GH biological actions. This study was aimed to evaluate whether GHR fl/d3 polymorphism contributes to the inter-individual variability of growth and metabolism in heathy children and adolescents. Methods: A total of 4730 students aged 6-16 years from Yixing and Suqian city in China were included in this cross-sectional study. Height and body mass index (BMI) were transformed into the form of z-score corresponding to age and gender. Logistic regression was used to evaluate the associations of GHR fl/d3 polymorphism with height, BMI, metabolic traits and hypertension by estimating the odds ratios (ORs) and 95% confidence intervals (CIs). Results: GHR d3 allele was inversely associated with overweight, but positively associated with increased total cholesterol (TC) and triglyceride (TG) levels (OR [95% CI] for overweight: 0.754 [0.593-0.959], P=0.021; OR [95% CI] for TC: 0.744 [0.614-0.902], P=0.003; OR [95% CI] for TG: 0.812 [0.654-0.998], P=0.047). GHR d3 allele was associated with decreased odds of pre-hypertension in boys (OR [95% CI]: 0.791 [0.645-0.971], P=0.025), but associated with increased odds of pre-hypertension and hypertension in girls (ORs [95% CIs]: 1.379 [1.106-1.719], P=0.004; OR [95% CI]: 1.240 [1.013-1.519], P=0.037). Interaction of GHR fl/d3 polymorphism with gender contributed to increased odds of pre-hypertension and hypertension (interactive ORs [95% CIs]: 1.735 [1.214-2.481], P=0.003; OR [95% CI]: 1.509 [1.092-2.086], P=0.013). Stratification analysis showed that the correlation tendencies of GHR fl/d3 polymorphism and BMI with age were different between two cities with discrepant economic development levels. Conclusion: GHR fl/d3 polymorphism is associated with growth, metabolism, and hypertension in children and adolescents with the gender specificity, and the genetic effect of GHR fl/d3 may be modified by the local socioeconomic levels.